A Polyamine-Based Dinitro-Naphthalimide Conjugate as Substrates for Polyamine Transporters Preferentially Accumulates in Cancer Cells and Minimizes Side Effects in vitro and in vivo - Ma, Jing; Li, Yingguang; Li, Linrong; Yue, Kexin; Liu, Hanfang; Wang, Jiajia; Xi, Zhuoqing; Shi, Man; Zhao, Sihan; Ma, Qi; Liu, Sitong; Guo, Shudi; et al. (Frontiers in Chemistry, 2020)
Naphthalimides, such as amonafide and mitonafide in clinical trials, have been developed as antitumor agents for orthotopic tumor. However, the serious side effects in cancer patients limit their applications. Herein, a new class of polyamine-based naphthalimide conjugates 5a-5c, 7a-7b, and 11a-11b with and without the alkylation of the distant nitrogen in the polyamine chain were synthesized and the mechanism was determined. Compared with amonafide, dinitro-naphthalimide conjugate 5c with a 4,3-cyclopropyl motif preferentially accumulates in cancer cells and minimizes side effects in vitro and in vivo. More importantly, 5c at the dosage of as low as 3 mg/kg (57.97%) displays better antitumor effects than the positive control amonafide (53.27%) at 5 mg/kg in vivo. And a remarkably elevated antitumor activity and a reduced toxicity are also observed for 5c at 5 mg/kg (65.90%). The upregulated p53 and the apoptotic cells (73.50%) indicate that the mechanism of 5c to induce apoptosis may result from its enhanced DNA damage. Further investigation indicates that in addition to target DNA, 5c can modulate the polyamine homeostasis by upregulating polyamine oxidase (PAO) in a different way from that of amonafide. And also by targeting PTs overexpressed in most of cancer cells, 5c downregulates the contents of Put, Spd, and Spm, which are in favor of suppressing fast-growing tumor cells. Our study implies a promising strategy for naphthalimide conjugates to treat hepatic carcinoma with notable activities and reduced toxicities at a low dosage.